2011
DOI: 10.1111/j.1365-2966.2011.19048.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and statistical properties of small-scale convective vortex-like motions in a quiet-Sun region

Abstract: High-resolution observations of a quiet-Sun internetwork region taken with the Solar 1-m Swedish Telescope in La Palma are analysed. We determine the location of small-scale vortex motions in the solar photospheric region by computing the horizontal proper motions of smallscale structures on time-series of images. These plasma convectively driven swirl motions are associated to (1) downdrafts (that have been commonly explained as corresponding to sites where the plasma is cooled down and hence returned to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 26 publications
8
39
0
Order By: Relevance
“…The same behavior is seen in the vorticity, with values that also reach −0.03 s −1 at τ 500 = 1, where negative means clockwise rotation. This value of vorticity is an order of magnitude larger than that detected with LCT (Bonet et al 2010;Vargas Domínguez et al 2011;Requerey et al 2017), but comparable to that found in simulations (e.g., Kitiashvili et al 2011).…”
Section: Small-scale Vortex Flowsupporting
confidence: 83%
See 3 more Smart Citations
“…The same behavior is seen in the vorticity, with values that also reach −0.03 s −1 at τ 500 = 1, where negative means clockwise rotation. This value of vorticity is an order of magnitude larger than that detected with LCT (Bonet et al 2010;Vargas Domínguez et al 2011;Requerey et al 2017), but comparable to that found in simulations (e.g., Kitiashvili et al 2011).…”
Section: Small-scale Vortex Flowsupporting
confidence: 83%
“…Such a cellular pattern is commonly found in both observations and hydrodynamical simulations when the LCT technique is applied to intensity images Muller et al 1992;Roudier et al 1998;Matloch et al 2010;Yelles Chaouche et al 2011;Requerey et al 2017). At the junction of mesogranular cells, smaller structures such as converging flows (Bonet et al 2010;Vargas Domínguez et al 2011;Requerey et al 2017) are also observed. The locations of the convergence centers are indicated by red circles in Figs.…”
Section: Comparison With Lctmentioning
confidence: 76%
See 2 more Smart Citations
“…On larger scales, rotational motions were observed in sunspots, and they are usually associated with energy and helicity buildup and later release by flare and/or coronal mass ejection (Brown et al, 2003;Hiremath and Suryanarayana, 2003;Hiremath et al, 2005;Yan and Qu, 2007;Yan et al, 2008Yan et al, , 2009Yan et al, , 2012Min and Chae, 2009;Kazachenko et al, 2010;Zhu et al, 2012;Jiang et al, 2012;Vemareddy et al, 2012Vemareddy et al, , 2016Hardersen et al, 2013;Wang et al, 2014Wang et al, , 2016Ruan et al, 2014;Gopasyuk, 2015;Li and Liu, 2015;Suryanarayana et al, 2015). The rotation of sunspots is usually very slow; this means that the evolution of the magnetic field in the corona associated with it would be slow as well.…”
Section: Introductionmentioning
confidence: 99%